The Persian Gulf in the coming decade : trends, threats, and opportunities - Byman, Daniel, 1967- (Rand, 2002)
Likely challenges to US interests in the Persian Gulf, key uncertainties and trends, and the implications of those trends for the USA are examined in this study. It concludes that while many trends in the region are positive, daunting problems remain.